Physiological and motor characteristics of long distance running depending on the level of preparedness - Mironova O.V.; Yarchikovskaya L.V.; Kuritsyna A.E.; Ustinova O.N.; Sharonova A.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study is to substantiate the relationship between the physiological and motor characteristics of long-distance running and the growth of sports achievements. Methods and structure of the study. The study involved 20 students involved in athletics and qualifying for long-distance running (group A (n=10) – II adult category, group B (n=10) – I adult category and above). The experiment used running tests on a treadmill, during which a complex of cardiorespiratory, metabolic and motor characteristics were recorded. Long-distance running is characterized by maximum mobilization of body systems. The study made it possible to establish that an increase in most of the studied physiological indicators indicates an increase in the functional capabilities of those involved, and with an increase in the preparedness of athletes, the energy cost of running decreases and the ratio of aerobic and anaerobic components of energy supply changes towards an increase in the share of the anaerobic component. Results and conclusions. The maximum values of a number of physiological parameters recorded during the 3000 m run were compared with the corresponding data obtained in tests on a treadmill, which made it possible to determine maximum aerobic and anaerobic capabilities. An increase in most of the studied indicators indicates an increase in the functional capabilities of the body of those involved. During the study, the following pattern was revealed: with increasing fitness of athletes, energy consumption during running decreases, and the ratio of aerobic and anaerobic energy supply modes changes towards an increase in the share of the anaerobic component.